Pengukuran Kualitas Layanan Sistem Kependudukan Online Menggunakan Metode E-Govqual dan IPA - Yahya, Muhammad Havian Nurdin; Sumirat, Lambang Probo; Santoso, Budi (STMIK Banjarbaru, 2024)
The Population and Civil Registration Office of Jombang Regency is one of the government agencies of Jombang Regency that has implemented E-Government. In this case, â€œDispendukcapilâ€ Jombang Regency created an information system called